SINERGI STRATEGI KONTEN DAN OPTIMASI MEDIA DALAM MENINGKATKAN KEBERHASILAN KAMPANYE MEDIA SOSIAL - Ni Putu Anna Saphira; Ni Kadek Suryani; Anita Heptariza (STKIP Subang, 2026)
This study aims to analyze the synergy between Content Strategy and Media Optimization in enhancing the success of social media campaigns, with Content Performance as a mediating variable. The research is motivated by the challenges digital agencies face in dealing with content saturation and dynamic algorithms, where high content production often does not correlate with campaign success. Using a quantitative approach through a case study design at MAVA Digital Marketing Agency, data were collected via questionnaires from the creative and campaign management teams. Data analysis was conducted using the Structural Equation Modeling approach via Partial Least Squares (PLS-SEM). The results indicate that a well-defined content strategy and precise media optimization significantly improve micro-level content performance. The key findings confirm that Content Performance serves as a crucial mediating bridge in transforming strategic inputs into macro-level campaign success. The study’s conclusion provides practical implications for digital agencies to integrate creative planning with distribution techniques to achieve optimal